Krabbe Disease: Prospects of Finding a Cure Using AAV Gene Therapy - Nasir, Gibran; Chopra, Rajiv; Elwood, Fiona; Ahmed, Seemin S. (Frontiers in Medicine, 2021)
Krabbe Disease (KD) is an autosomal metabolic disorder that affects both the central and peripheral nervous systems. It is caused by a functional deficiency of the lysosomal enzyme, galactocerebrosidase (GALC), resulting in an accumulation of the toxic metabolite, psychosine. Psychosine accumulation affects many different cellular pathways, leading to severe demyelination. Although there is currently no effective therapy for Krabbe disease, recent gene therapy-based approaches in animal models have indicated a promising outlook for clinical treatment. This review highlights recent findings in the pathogenesis of Krabbe disease, and evaluates AAV-based gene therapy as a promising strategy for treating this devastating pediatric disease.